ANTIDIABETIC ACTIVITY AND MODULATION OF ANTIOXIDANT STATUS BY OCIMUM CANUM IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - Alok Kumar Dash; Jhansee Mishra; Deepak Kumar Dash (European Scientific Journal, ESJ, 2014)
The aquous extract of Ocimum Canum. (Family: Lamiaceae) leaf was investigated for its antidiabetic effect in Wistar Albino rats. Diabetes was induced in Albino rats by administration of streptozotocin (45mg/kg, I.P). The aquous extractof Ocimum canum at a dose of 100mg/kg and 200mg/kg of body weight was administered to diabetes induced rats for a period of 28 days. The effect of aquous extractof Ocimum canum leaf extract on blood glucose, plasma insulin, glycosylated haemoglobin, serum lipid profile low density lipoprotein (LDL), very low density lipoprotein (VLDL), high density lipoprotein (HDL), atherogenic index and the activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP) of all groups were analyzed.Antioxidant enzymes catalase (CAT), superoxide dismutase (SOD), reduced glutathione (GSH) , serum thiobarbituric (TBAR) were measured in the diabetic rats. The aquous extractof Ocimum canum leaf elicited significant reductions of blood glucose (p<0.01), lipid parameters except HDL-C, serum enzymes and significantly increased HDL-C and antioxidant enzymes.. From the above results it is concluded that aquous extractof Ocimum canum possesses significant antidiabetic, antihyperlipidaemic and antioxidant effects in streptozotocin induced diabetic rats.